ANALISIS (SWOT) KEBIJAKAN KEPEMIMPINAN DI INDONESIA - Nanda Inka Fitri; Zu’ama Anggun Larasati; Nirva Diana; Eti Hadiati; Meriyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to comprehensively analyze the condition of national and regional leadership in Indonesia through a SWOT approach to map the strengths, weaknesses, opportunities, and threats that influence the effectiveness of policy formulation and implementation. Using a descriptive qualitative method and document analysis, this study draws on various secondary sources, including national and international policy reports, scholarly articles, academic books, and governance data such as the World Governance Indicators and the Corruption Perceptions Index. The analysis was carried out through data reduction, categorization, synthesis, and source triangulation to ensure information validity. The findings reveal that Indonesian leadership possesses several internal strengths, such as democratic legitimacy through direct elections, a wide and potentially powerful bureaucratic structure, progress in government digitalization, and strong social capital. However, structural weaknesses remain dominant, including political fragmentation, overlapping bureaucratic authorities, disparities in regional capacity, limited use of data in policymaking, and a tendency toward personalized leadership. Externally, Indonesia faces significant opportunities such as the demographic bonus, digital transformation acceleration, increased civil society participation, and international cooperation. Nonetheless, leadership also confronts threats such as global economic uncertainty, geopolitical tensions in the Indo-Pacific, political polarization and digital disinformation, widening social inequality, and the risks of natural disasters and environmental crises. The implications of this study emphasize the need for more adaptive, data-driven, and long-term-oriented leadership strategies through strengthened bureaucratic meritocracy, political consolidation, integrated digital governance, and strategic diplomacy in responding to global pressures. The novelty of this research lies in integrating leadership analysis with the SWOT framework into a systematic evaluative model, along with the use of contemporary empirical cases in the post-bureaucratic reform and digital governance era as the basis for strategic mapping. This approach provides a deeper understanding of the strategic position of Indonesian leadership amid increasingly complex global socio-political dynamics and offers relevant policy recommendations for strengthening governance in the future.